AlGaN-based ultraviolet light-emitting diodes on sputter-deposited AlN templates with epitaxial AlN/AlGaN superlattices. (January 2018) - Zhao, Lu; Zhang, Shuo; Zhang, Yun; Yan, Jianchang; Zhang, Lian; Ai, Yujie; Guo, Yanan; Ni, Ruxue; Wang, Junxi; Li, Jinmin
Abstract: We demonstrate AlGaN-based ultraviolet light-emitting diodes (UV-LEDs) grown by metalorganic chemical vapor deposition (MOCVD) on sputter-deposited AlN templates upon sapphire substrates. An AlN/AlGaN superlattices structure is inserted as a dislocation filter between the LED structure and the AlN template. The full width at half maximum values for (0002) and (10 1 ¯ 2) X-ray rocking curves of the n-type Al0.56 Ga0.44 N layer are 513 and 1205 arcsec, respectively, with the surface roughness of 0.52 nm. The electron concentration and mobility measured by Hall measurement are 9.3 × 10 17 cm −3 and 54 cm 2 /V·s at room temperature, respectively. The light output power of a 282-nm LED reaches 0.28 mW at 20 mA with an external quantum efficiency of 0.32%. And the values of leakage current and forward voltage of the LEDs are ∼3 nA at −10 V and 6.9 V at 20 mA, respectively, showing good electrical performance. It is expected that the cost of the UV-LED can be reduced by using sputter-deposited AlN template. Highlights: AlGaN-based UV-LEDs on sputtered AlN templates are realized, without commonly used MOCVD-grown AlN templates. With the use of the sputtered AlN template, the cost of the UV-LEDs could be reduced. The 200 nm AlN template is proved to be better to improve the epitaxial crystal quality and performance of the UV-LED.